Lifetime of environmental/thermal barrier coatings deposited on a niobium silicide composite with boron containing M7Si6‐based bond coat. Issue 12 (6th September 2016) - Braun, R.; Lange, A.; Schulz, U.; Portebois, L.; Mathieu, S.; Vilasi, M.; Drawin, S.
Abstract : Environmental/thermal barrier coatings (E/TBCs) of yttria partially stabilised zirconia (YSZ), gadolinium zirconate (GZO) and a combination of Y2 SiO5 and GZO were applied on a Nb/Nb5 Si3 ‐based alloy with the nominal composition of Nb‐25Ti‐8Hf‐2Cr‐2Al‐16Si (at%). A B‐containing M7 Si6 ‐based (M = Ti, Nb, Fe, Cr) layer produced by pack cementation was used as bond coat. The ceramic topcoats were manufactured by electron‐beam physical vapour deposition (YSZ and GZO) and magnetron sputtering (Y2 SiO5 ). The different E/TBC systems were tested under cyclic oxidation conditions in air at 1100 and 1200 °C. Lifetimes exceeding 1000 cycles of 1 h dwell time at 1100 °C were determined. The YSZ, GZO and combined Y2 SiO5 + GZO topcoats did not spall off during the maximum exposure time, exhibiting good adherence to the thermally grown oxide scale which consisted of mixed oxides of Fe, Ti, Cr and Nb embedded in silica. For the E/TBC systems with YSZ and GZO which were thermally cycled at 1200 °C, lifetimes up to 850 cycles were measured; that of the system with a combined Y2 SiO5 + GZO topcoat exceeded again 1000 cycles. Abstract : On an Nb/Nb5 Si3 ‐based alloy, a potential ultra‐high temperature material, oxidation protective coatings and ceramic topcoats were deposited reproducing thermal barrier coating systems applied on Ni‐based superalloys. These environmental protective systems of yttria partially stabilised zirconia and gadolinium zirconate topcoats with chromia‐silica forming bond coat show a remarkable performance during thermal cycling tests at 1100 and 1200 °C in air.